Negative fitness effects of Wolbachia infection in Drosophila sturtevanti - Moreira, Marina Magalhães (2020)
Natural Selection favors the fittest individuals in a given population, while the genetic drift can increase or decrease by chance the frequency of a given character. In this sense, both natural selection and genetic drift affect the prevalence of endosymbionts. Wolbachia is an alpha-proteobacteria that in- fects 52 % of arthropods. It is primarily transferred from the mothers to their offspring (vertical transfer). Wolbachia remains in a given population of hosts by increasing their fitness or through reproductive phenotypes that manipulate the hosts, such as the cytoplasmic incompatibility (CI) or male- killing (MK). Alternatively, it can stay by chance through a perfect (100 %) vertical transmission. In this work, we investigated the relation- ship between Wolbachia and Drosophila sturtevanti, a Neotropical species that presumably acquired the infection through horizontal transfer. In our first sampling effort, performed in several sampling points in Minas Gerais, between 2015 and 2016, we found 100 % of individuals infected by wStv MI, the same strain found in some D. sturtevanti lineages sampled in Panama. The success of antibiotic treatment showed that D. sturtevanti does not de- pend on the bacteria to survive and reproduce. We thus crossed different combinations of infected and non-infected individuals with the same ge- netic background to measure the fitness components of the infection and test whether wStv MI induces reproductive phenotypes in D. sturtevanti. We found no evidence of CI or MK. Also, Wolbachia seems to reduce the fitness of infected hosts. Given these results, we performed a new sampling in the UFV population in 2019 to investigate the rate of vertical transmis- sion. Surprisingly, only 50 % of the samples were infected and presented an almost perfect vertical transmission. Such a result suggests that the prevalence of Wolbachia is declining in the UFV D. sturtevanti population. On the other hand, given the connectivity of D. sturtevanti populations, Wolbachia prevalence may fluctuate due to the arrival of infected individuals from other populations. New field samplings, over long time intervals, and the investigation of the effects of Wolbachia in a populational approach will help us to understand the epidemiological dynamics of Wolbachia in the UFV D. sturtevanti population. Keywords: Neotropical Drosophila. Controled Crosses. Field Sampling. Molecular Characterization.